Implementation of Discovery Learning Model Assisted by E-Module to Improve Students' Critical Thinking Skills on Global Warming Material Quantitative Study - Nisrina, Ismi; Saputra, Hendri; Efendi, Ridwan (Department of Physics Education, Universitas Mataram, 2024)
Critical thinking skills are one of the competencies that students must have in the 21st century. Students' critical thinking skills in Indonesia are still categorized as low because these skills are not provided in learning activities, especially in physics subjects. This study aims to determine the effectiveness of applying the discovery learning model with the help of e-modules in improving students' critical thinking skills on global warming material. Quantitative method with Pre-Experimental Design design in the form of One Group Pretest-Postest. The research sample amounted to 30 students from one of the State Madrasah Aliyah in Garut Regency, which was selected through random sampling technique. This research instrument consists of 5 essay questions that measure critical thinking skills and 16 questionnaire statements to measure student responses. The research data obtained were analyzed using the Normalized Gain test for essay questions and percentages for student response questionnaires. The results showed an increase in the N-Gain of students' critical thinking skills of 0.66 with a moderate category. While for the student response questionnaire after learning activities with a positive interpretation. This shows that discovery learning assisted by e-module on global warming material can improve students' critical thinking skills. The application of the discovery learning model with the help of e-modules can be an effective strategy to improve students' critical thinking skills, especially on global warming material. Physics teachers can consider using it to better prepare students for the challenges of the 21st century.